To segregate, or to discriminate-that is the question : experiment on identity and social preferences (2020)
How do various sources of social identity affect segregation and discrimination decisions? In our laboratory experiment, social identity originates either from similar preferences, income, abil- ity, randomly or from shared socioeconomic status. For the latter, we exploit Colombia's unique (public information) stratification system which assigns households to socioeconomic strata based on its residential block amenities. Subjects decide with whom to in- teract in a Dictator and Trust Game. We find high socioeconomic status senders segregate against out-group receivers in the Dicta- tor Game, while low socioeconomic ones do so in the Trust Game. This segregation pattern is partly explained by payoff-maximizing behavior. In the Trust Game, we gather evidence for statistical discrimination. In the Dictator Game, evidence points to a taste for redistribution when identity originates from socioeconomic sta- tus or income level. No matter the source of identity, our subjects expect being segregated but not discriminated against.